Infrastructural Cinema: Seeing Energy on Film in the Long 1930s - (:unkn) unknown (My University, 2023)
American energy and infrastructure are at points of major reckoning. Electrical grids suffer major outages, while climate change threatens every known way of harnessing energy resources. But how did we get here? My dissertation, “Infrastructural Cinema: Seeing Energy on Film in the Long 1930s” analyzes the characterization of energy resources in American government and corporate films from the 1920s-1930s, or “infrastructural cinema.” Specifically, I interrogate how infrastructural cinema has affected our understanding of how to control and manage energy, and to what extent our reliance on such infrastructures limits present-day energy solutions. Infrastructural cinema is concerned with how energy and its networks are made cinematic: how does film both mediate our understanding of natural resources and act as an infrastructure itself? It is a concept born at the nexus of modernity, media, aesthetics, technology, ecology, and the nonhuman. I pursue infrastructural cinema as a media technology and a cultural technology—an ideological apparatus—often kept hidden from sight. This analysis reveals the intentionality of both energy and filmic systems that may otherwise be invisible or normalized, even to the point of being interpreted as neutral. Such a history of infrastructural cinema focuses on the constructedness of both cinema and infrastructure and questions the acceptance of certain infrastructures as central to human culture, primarily those that extract, transform, harness, or deliver natural resources to humans as energy. For example, the “pipelines alive with racing oil” deemed necessary in More Power To You (1939) crisscross native land and threaten ecologies. My first chapter historicizes nonfiction film and focuses on the sociocultural context of the 1920s-1930s. Chapters 2, 3, and 4 analyze films about hydroelectric dams, oil and gas infrastructure, and electrical infrastructure respectively. Understanding this archive offers ways to address the infrastructural zeitgeist of the present and encourages new visions for life after energy extraction.
Keywords: Documentary; Energy Humanities; Environmental Humanities; Film Aesthetics; Film History; Infrastructure